Towards Tourism Business Change - Eyal ECKHAUS (Revista de Management Comparat International)
The tourism industry is a critical component in the global economy being the world’s largest generator of wealth and employment. The widespread use of the internet has had a tremendous impact on the industry which was one of the first to take advantage of the capabilities and developments. Despite these advances, the tourism industry still hasn't realized the full potential of the digital realm and much need to be done to attain a higher level of user experience. A major recent technological advance has been the integration of a three-dimensional virtual world into a virtual reality. This new environment is rapidly growing in popularity among users and businesses as powerful promotional tool. Despite the potential of this new type of environment, a question-mark still hangs over its implementation and assimilation. This paper discusses the implications of this novel development in relation to the tourism industry, and highlights the approaching trend.